Pemahaman Karyawan tentang Lingkungan Kerja Nyaman dan Produktivitas di Rumah Makan Masakan Jawa Bu Socheh - Ireina Tsaqila; Sugeng Pradikto (Student Research Journal, 2025)
This research is to understand employee perceptions of a comfortable working environment and its impact on productivity at the Bu Socheh Javanese Food Restaurant. A good work environment, both from physical and psychological aspects, greatly influences the enthusiasm and work efficiency of employees in the culinary industry. The research used is a qualitative approach with data collection techniques through in-depth interviews, observation and documentation. The research subjects consisted of employees who worked in various parts of the restaurant, including the kitchen, service and administration. Research shows that employees consider a comfortable work environment to include a clean workplace, ergonomic layout, harmonious working relationships, and support from superiors. The factors that most influence work comfort are cleanliness and good ventilation, because they can improve health and work efficiency. However, several obstacles were found, such as the increasing number of flies during the rainy season, limited kitchen space, and lack of rest facilities for employees. These obstacles hinder work comfort and can reduce productivity. The conclusion of this research is that a comfortable work environment contributes directly to increasing employee productivity. To improve working conditions, it is recommended that restaurant managers improve their layout, provide supporting facilities, and implement strategies to overcome environmental problems, such as managing cleanliness and handling flies during the rainy season. In this way, employees can work more comfortably and optimally, thus improving the quality of service to customers.